Preparation and Evaluation of Lercanidipine HCl Nanosuspension to Improve the Dissolution Rate - Zahraa A. Alsafar; Fatima J. Jawad (Iraqi Journal of Pharmaceutical Sciences, 2025)
Lercanidipine HCl, a third-generation calcium channel blocker, blocks calcium entry into smooth muscle L-type calcium channels. This action leads to a decrease in blood pressure and induces peripheral vasodilation. Lercanidipine HCl belongs to the Biopharmaceutical classification system class II category of drugs. It is practically insoluble in water and has high solubility in methanol. The oral bioavailability of lercanidipine HCl is 10%, and irregular absorption due to its poor solubility and significant first-pass metabolism. This study aimed to produce and evaluate the nanosuspension of lercanidipine HCl with improved solubility and dissolution rates. The research used the solvent/antisolvent precipitation technique to generate a nanosuspension, using different stabilizers at various concentrations. The study examined the impact of several procedure factors on the particle size and polydispersity index of chosen lercanidipine HCl nanosuspension formulations. The evaluation parameters comprised particle size, polydispersity index, drug content, entrapment efficiency, and in-vitro dissolution rates. Together, these characteristics assisted in determining the optimum formula for lercanidipine HCl nanosuspension. The optimal formula (F2) has a particle size of 92.94 nm and a polydispersity index of 0.2515. It consisted of soluplus as a stabilizer in a ratio of 1:2 and a solvent: antisolvent ratio of 3:10 with a stirring speed of 1500 rpm, and EE% was 97.76%. The prepared formulation significantly improved the dissolution rate of lercanidipine HCl compared to the pure drug. The release profiles of formula (F2) reached 100% within 20 minutes. This formula was examined for surface morphology using Field emission scanning electron microscope, and the optimized nanoparticles generated by the lyophilization procedure were assessed for compatibility using Fourier Transform Infrared Spectroscopy and for its crystalline state using X-ray powder diffraction. Research results indicate that using the solvent anti-solvent technique for producing lercanidipine HCl nanosuspension exhibits its effectively enhances the dissolution rate of lercanidipine HCl.